Managing player load in professional rugby union: a review of current knowledge and practices. Issue 5 (9th August 2016) - Quarrie, Kenneth L; Raftery, Martin; Blackie, Josh; Cook, Christian J; Fuller, Colin W; Gabbett, Tim J; Gray, Andrew J; Gill, Nicholas; Hennessy, Liam; Kemp, Simon; Lambert, Mike; Nichol, Rob; et al.
Abstract : Background: The loads to which professional rugby players are subjected has been identified as a concern by coaches, players and administrators. In November 2014, World Rugby commissioned an expert group to identify the physical demands and non-physical load issues associated with participation in professional rugby. Objective: To describe the current state of knowledge about the loads encountered by professional rugby players and the implications for their physical and mental health. Findings: The group defined 'load' as it relates to professional rugby players as the total stressors and demands applied to the players. In the 2013–2014 seasons, 40% of professional players appeared in 20 matches or more, and 5% of players appeared in 30 matches or more. Matches account for ∼5–11% of exposure to rugby-related activities (matches, team and individual training sessions) during professional competitions. The match injury rate is about 27 times higher than that in training. The working group surmised that players entering a new level of play, players with unresolved previous injuries, players who are relatively older and players who are subjected to rapid increases in load are probably at increased risk of injury. A mix of 'objective' and 'subjective' measures in conjunction with effective communication among team staff and between staff and players was held to be the best approach to monitoring and managing player loads. While comprehensive monitoring holds promise for individually addressing player loads, it brings with it ethical and legal responsibilities that rugby organisations need to address to ensure that players' personal information is adequately protected. Conclusions: Administrators, broadcasters, team owners, team staff and the players themselves have important roles in balancing the desire to have the 'best players' on the field with the ongoing health of players. In contrast, the coaching, fitness and medical staff exert significant control over the activities, duration and intensity of training sessions. If load is a major risk factor for injury, then managing training loads should be an important element in enabling players to perform in a fit state as often as possible.